2017
DOI: 10.1038/cddis.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular histone in organ injury

Abstract: Histones are intra-nuclear cationic proteins that are present in all eukaryotic cells and are highly conserved across species. Within the nucleus, they provide structural stability to chromatin and regulate gene expression. Histone may be released into the extracellular space in three forms: freely, as a DNA-bound nucleosome or as part of neutrophil extracellular traps, and all three can be detected in serum after significant cellular death such as sepsis, trauma, ischaemia/reperfusion injury and autoimmune di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
217
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(221 citation statements)
references
References 109 publications
(158 reference statements)
2
217
0
2
Order By: Relevance
“…However, it remains difficult to determine whether this is the case as there is a lack of antibodies that can clearly distinguish between the two histone forms. 41,42 Although in our study we did not directly address the role of histones, using TLR reporter lines we demonstrated that NET fragments elicited potent TLR2 and -4 activation that could be mostly extinguished by complete digestion of NETs. We also observed that NET fragments stimulated TLR9 activation.…”
Section: Discussionmentioning
confidence: 70%
“…However, it remains difficult to determine whether this is the case as there is a lack of antibodies that can clearly distinguish between the two histone forms. 41,42 Although in our study we did not directly address the role of histones, using TLR reporter lines we demonstrated that NET fragments elicited potent TLR2 and -4 activation that could be mostly extinguished by complete digestion of NETs. We also observed that NET fragments stimulated TLR9 activation.…”
Section: Discussionmentioning
confidence: 70%
“…Release of nucleosomes is considered to reflect cell death . Elevated circulating levels of nucleosomes have been detected in several conditions, including trauma, ischemia–reperfusion injury, and sepsis .…”
Section: Discussionmentioning
confidence: 99%
“…Because of this limitation, subjects received ASCs prior to LPS, whereas posttreatment would better resemble the clinical scenario. Release of nucleosomes is considered to reflect cell death [78,79]. Elevated circulating levels of nucleosomes have been detected in several conditions, including trauma, ischemiareperfusion injury, and sepsis [49,50,78,79].…”
Section: Discussionmentioning
confidence: 99%
“…In this same work, it was verified that this antimicrobial response was due to the protein content of this organelle, mainly due to the action of histones. 32 Despite being a cationic protein canonically involved in the formation and maintenance of nucleosomes, 130 histones are cytotoxic in vitro and in vivo when located in the extracellular environment, or when in excess in the cytoplasm, furthermore, they have a strong ability to kill bacteria [130][131][132] (Fig. 1).…”
Section: Ld Functions In Bacterial Infectionmentioning
confidence: 99%